Elongation method with intermediate mechanical and electrostatic embedding for geometry optimizations of polymers. Issue 25 (30th July 2020) - Mashkovtsev, Denis; Mizukami, Wataru; Korchowiec, Jacek; Stachowicz‐Kuśnierz, Anna; Aoki, Yuriko
Abstract: The elongation method with intermediate mechanical and electrostatic embedding (ELG‐IMEE) is proposed. The electrostatic embedding uses atomic charges generated by a charge sensitivity analysis (CSA) method and parameterized for three different population analyses, namely, the Merz–Singh–Kollman scheme, the charge model 5, and the atomic polar tensor. The obtained CSA models were tested on two model systems. Test calculations show that the electrostatic embedding provides several times of decrease in the difference of energies of testing and reference calculations in comparison with the conventional elongation approach (ELG). The mechanical embedding is implemented in a combination of the conventional elongation method and the ONIOM approach. Moreover, it was demonstrated that the geometry optimization with the ELG‐IMEE reduces the errors in the optimized structures by about one order in root‐mean‐square deviation, when compared to ELG. Abstract : Elongation, a reduced‐scaling method for ab initio simulation of polymers, is combined with the ONIOM approach to improve geometry optimization calculations of polymers. A proof of concept implementation of this approach is done in this work including a modification of the elongation with electrostatic embedding. Geometry optimizations of several testing polymers with the proposed approach exhibit notable improvement in the results compared to the conventional elongation calculation.